2021
DOI: 10.1523/eneuro.0143-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Behavioral and Brainstem Transcriptomic Neuroadaptations following Neonatal Opioid Exposure in Outbred Mice

Abstract: The opioid epidemic led to an increase in the number of Neonatal Opioid Withdrawal Syndrome (NOWS) cases in infants born to opioid-dependent mothers. Hallmark features of NOWS include weight loss, severe irritability, respiratory problems, and sleep fragmentation. Mouse models provide an opportunity to identify brain mechanisms that contribute to NOWS. Neonatal outbred Swiss Webster Cartworth Farms White (CFW) mice were administered morphine (15mg/kg, s.c.) twice daily for postnatal days (P) 1-14, an approxima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 101 publications
4
23
1
Order By: Relevance
“…Gene CDH1 participates in neurogenesis and cortical development and was under-expressed in the morphine-treated relative to the saline group ( Table 2 ). This pattern is aligned with reports of reduced expression in the brainstems of morphine-exposed female mice [ 57 ].…”
Section: Discussionsupporting
confidence: 90%
“…Gene CDH1 participates in neurogenesis and cortical development and was under-expressed in the morphine-treated relative to the saline group ( Table 2 ). This pattern is aligned with reports of reduced expression in the brainstems of morphine-exposed female mice [ 57 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our results, one study found that offspring from oxycodone-exposed dams have higher frequency USVs than control offspring (Zanni et al, 2021). Another study also found that neonate offspring injected with morphine from PND 1 -14 had increased USV frequency parameters (Borrelli et al, 2021).…”
Section: -Discussionsupporting
confidence: 90%
“…Seven articles investigated both sexes (n=7, 12%), using surprisingly low sample sizes (n=1-4 in male/female, and opioid-treated/control, groups; Fig.2D). Among these, 2 studies treated sex as a covariate [22,23], and 3 pooled both sexes for the analysis of opioid effects [2426], therefore providing no direct description of male/female differences. This is concerning, considering that the 2 remaining studies found little overlap, from 5 to 35% (see [27] and [28]), among morphine-induced changes occurring in each sex.…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, a large majority focused on the mesocorticolimbic dopaminergic pathway: the NAc (21 articles [8,22,26,2830,32,4053]), frontal cortex (13 articles [8,25,27,29,51,5461]), whole/unspecified striatal complex (11 articles [24,33,6270]), dorsal striatum (7 articles [8,30,4850,71,72]) and ventral tegmental area (VTA, 5 articles [28,51,7375]). Other regions included the spinal cord (7 articles [62,7681]); hippocampus (5 articles [8,63,8284]); amygdala (3 articles [8,85,86]); locus coeruleus [74, 87], ventral midbrain [42, 88], hypothalamus [89, 90], whole brain with [91] or without [92] cerebellum (1 each); periaqueductal gray matter [93], pituitary gland [90], arcuate nucleus [94], nucleus of the tractus solitarius [31], brainstem [23], cerebellum [84] or dorsal root ganglia [95] (DRG, 1 each). Below, we briefly describe the rationale for studying such diverse structures.…”
Section: Resultsmentioning
confidence: 99%